2004
DOI: 10.1111/j.1774-9987.2004.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response Study of 22‐Oxacalcitriol in Patients with Secondary Hyperparathyroidism

Abstract: The dose-response relationships and the safety of administering 22-oxacalcitriol (OCT) to patients with secondary hyperparathyroidism (2HPT) under regular three-times-weekly hemodialysis (HD) were evaluated by double-blind parallel group design. A total of 203 patients with 2HPT were randomly allocated into four groups, and 5 mg (Group L), 10 mg (Group M), or 15 mg (Group H) OCT, or placebo (Group P) was administrated at the end of every HD for 12 weeks. Reductions of intactparathyroid hormone (iPTH) concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
(15 reference statements)
1
15
0
1
Order By: Relevance
“…Clinical trials in hemodialysis patients confirmed that OCT was effective in suppressing PTH levels (Akizawa et al, 2002(Akizawa et al, , 2004Hayashi et al, 2004;Tamura et al, 2005;Yasuda et al, 2003). Initial studies attained the targeted reduction in PTH (À30%) in 51% of the patients in a 1-year protocol (Akizawa et al, 2002), and in 44% (Yasuda et al, 2003) and 77% (Akizawa et al, 2004) of the patients treated for 12 weeks.…”
Section: Ed-71mentioning
confidence: 85%
See 2 more Smart Citations
“…Clinical trials in hemodialysis patients confirmed that OCT was effective in suppressing PTH levels (Akizawa et al, 2002(Akizawa et al, , 2004Hayashi et al, 2004;Tamura et al, 2005;Yasuda et al, 2003). Initial studies attained the targeted reduction in PTH (À30%) in 51% of the patients in a 1-year protocol (Akizawa et al, 2002), and in 44% (Yasuda et al, 2003) and 77% (Akizawa et al, 2004) of the patients treated for 12 weeks.…”
Section: Ed-71mentioning
confidence: 85%
“…Initial studies attained the targeted reduction in PTH (À30%) in 51% of the patients in a 1-year protocol (Akizawa et al, 2002), and in 44% (Yasuda et al, 2003) and 77% (Akizawa et al, 2004) of the patients treated for 12 weeks. As expected, higher doses suppressed PTH more effectively and were associated with higher frequency of hypercalcemia (Akizawa et al, 2004).…”
Section: Ed-71mentioning
confidence: 99%
See 1 more Smart Citation
“…Maxacalcitol has been shown to result in less hypercalcemia in animal models, but this has not translated into clinical trials 230 . In humans maxacalcitol has been shown to be effective in suppressing PTH levels 231233 , but in a study of 124 dialysis patients treated with maxacalcitol, 41 experienced hypercalcemia 232 . There is a dose-dependent relationship between the dose of maxacalcitol and risk of hypercalcemia 231 .…”
Section: Vitamin D Analogs In the Treatment Of Hyperparathyroidism Inmentioning
confidence: 99%
“…1,4,62 However, treatment with these drugs is limited in many cases because of hypercalcemia and hyperphosphatemia, particularly when they are used in conjunction with Ca-containing P binders. 1,2,63 Consequently, hypercalcemia, hyperphosphatemia, and a high Ca × P product lead to vascular and soft tissue calcifi cation.…”
Section: Vitamin D Analoguesmentioning
confidence: 99%